PENGARUH PENDEKATAN IMPLEMENTATION INTENTION DALAM MANAJEMEN PERAWATAN DIRI PADA PASIEN DIABETES MELLITUS TIPE 2 - Purnama Sari, Dewi; Kusnanto, Kusnanto; Yunitasari, Esti (Jurnal Ilmiah Kesehatan (Journal of Health Sciences), 2017)
Education about self-care DM type 2 has been given, but the failure rate in achieving glycemic control is still high. This leads to the risk of Diabetes Mellitus complications referring to the high cost of care. Action of self-care management of patients with type 2 diabetes is based on the intention. However, intention can not always be an action because of the barrier of self-control (self regulatory problem). Implementation intention becomes an effort in improving the realization of intention into action. This study aims to analyze the influence of implementation intention approach in the self-care management of type 2 Diabetes Mellitus patients. This study uses the quasy experiment method (pre-post test with control design) with comparing the effect of implementation intention in 2 group. The study was conducted in Internal Medicine Outpatient Ward in University of Airlangga Hospital with a total sample of 38 people with hypothesis test formula data proportion of two populations 1 tailed. Variable include action of nutrition management, modification of physical activity, medication adherence and self monitoring blood glucose measures using a questionnaire instrument. Data were analyzed through independent t-test. The result of the research shows that p value < tolerance level with α = 0,05 means that Ho is rejected, so there is an influence between implementation intention approach with nutrition management, modification of physical activity, and medication compliance. Whereas if obtained p value > tolerance level means Ho accepted, so there is no effect of implementation implementation approach with self monitoring of blood glucose. Conclusions: the impelementation intention approach improves the application of self-care management in nutrition management, modification of activity and medication adherence but can not improve action in independent self monitoring blood glucose (SMBG). Reccomendation: Further research can develop SMBG variables by providing standardized assessment based on patient needs and situations; allowing more than 4 weeks, grouping respondents homogeneously based on individual characteristics.